ENHANCING ENGLISH LANGUAGE SKILLS OFEFL STUDENTS IN THAILAND’S EEC CONTEXT THROUGH PROJECT-BASED LEARNING - Laksanasut, Saharat (SEAMEO QITEP in Language, 2024)
This quasi-experimental study investigated the impact of Project-Based Learning (PBL) on the English-speaking skills of Grade 9 students at Angsilapittayakom School in Thailand’s Eastern Economic Corridor (EEC). Recognizing the critical role of English proficiency in accessing global economic opportunities, the study compared PBL with traditional Communicative Language Teaching (CLT) methods. Seventy-seven students participated, with 39 in the experimental group engaging in PBL and 38 in the control group receiving CLT-based instruction. The intervention spanned eight weeks during the 2024 academic year. Research instruments included PBL and CLT lesson plans, along with pre- and post-tests measuring English-speaking skills. Data were analysed using paired sample t-tests and independent sample t-tests. The results showed that the experimental group’s post-test speaking skills improved significantly compared to their pre-test scores (p < .01). Additionally, the experimental group significantly outperformed the control group in post-test speaking skills (p < .01), demonstrating the effectiveness of PBL in fostering language acquisition. This study provided evidence that PBL could revolutionize English instruction by promoting active, inquiry-driven learning and addressing the limitations of traditional methods. PBL not only enhanced language proficiency but also better prepared students for real-world communication in dynamic economic contexts like the EEC. These findings offered valuable insights for educators and policymakers seeking innovative, skill-focused pedagogies aligned with 21st-century educational goals. Moreover, the results will be beneficial to language teachers worldwide, offering a practical framework to improve language learning outcomes and equip students for future success in globalized environments.